2008
DOI: 10.1590/s0004-282x2008000100007
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Parkinson’s disease: analysis of 50 cases in a clinic of movement disorders

Abstract: -Introduction:Pain is a common symptom in Parkinson's disease (PD), and is often related to the illness itself. Objective: To prospectively establish the ocurrence of pain in PD patients. Method: This study was conducted within a population composed of 50 patients with PD to evaluate the presence of pain. Results: Twenty-eight patients reported pain; comparing the group with pain and the group without pain, there were no differences related to the beginning of the illness and the motor symptoms of PD. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
0
24
0
1
Order By: Relevance
“…The two groups did not differ in terms of anxiety. Pain is an important aspect of PD10–12 and MSA13, 14 in which multiple mechanisms, including hypoperfusion, rheumatic, sensory, dystonic and off‐period related aspects have been postulated. In a previous study, MSA with predominant parkinsonism was associated with more pain than MSA with predominant cerebellar ataxia 2.…”
Section: Discussionmentioning
confidence: 99%
“…The two groups did not differ in terms of anxiety. Pain is an important aspect of PD10–12 and MSA13, 14 in which multiple mechanisms, including hypoperfusion, rheumatic, sensory, dystonic and off‐period related aspects have been postulated. In a previous study, MSA with predominant parkinsonism was associated with more pain than MSA with predominant cerebellar ataxia 2.…”
Section: Discussionmentioning
confidence: 99%
“…Complaints of pain and sensory disturbances are common NMS in PD and can affect up to 65% of patients, 58,65,[121][122][123][124][125] and a few studies have reported that PD patients may have a lower pain threshold. 126 Importantly, the impact of their presence on quality of life can be greater than that of motor features, 127,128 with pain as the sensory NMF with the greatest negative impact.…”
Section: Autonomic Fluctuationsmentioning
confidence: 99%
“…Distortions of body image are thought to be common in some pain states 9 . Pain may be a complain in more than 50% of PD patients 10 . It has been suggested that if body image relates to pain, treating body image may reduce pain, and treating pain may normalize body image 9,10 .…”
mentioning
confidence: 99%
“…Pain may be a complain in more than 50% of PD patients 10 . It has been suggested that if body image relates to pain, treating body image may reduce pain, and treating pain may normalize body image 9,10 . A neurological dysfunction could unleash not only alterations in the body image because of the illness itself, but also because of the reaction of the individual who, to preserve their body image, ends up modifying their body image depending on the perceived experiences resulting from the dysfunction suffered.…”
mentioning
confidence: 99%